Pengukuran Nilai ï¨ dan ïº Larutan Gliserin Terimbas pada Frekuensi PLN - Firdausi, K. Sofjan; Lego, Dro Dwi; Sugito, Heri (BERKALA FISIKA, 2007)
The magnetooptical specific rotary power h and frequence specific rotary power z have been measured in the glycerine through the interaction between external magnetic field modulated at 50-60 Hz and modulated laser light at the wavelength of 632,8 nm and 532 nm. The sample induced by the magnetic field that has the maximum value of 170 mT. The source of light of 632,8 nm and 532 nm is modulated between 30 Hz and 100 Hz. The result of experiment indicates that values of h and z at l = 632,8 nm are more dominant than at l = 532 nm.Â  Â  Key words: magnetooptic, specific rotary power, resonance frequency